DIAGNOSTIC KARATE TESTS - Dragan Doder (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The basic condition of a successful process of karate training is making diagnosis of any sportsman. Assessment is usually done by a coach and it is a part of technical process; quantity measurements are also a part of the evaluation which contains these tests. The suggested diagnostic karate tests are based on the knowledge of the specific karate characteristics and on the research which was done so far (Zulić 1985, Milošević and Zulić 1988, Jovanović 1981, 1988, Mudrić 1994, Doder 1998, 2000, 2005, Babiak, Doder, Savić, Golik2001, Savić, Doder, Babiak 2002). Karate as a type of sport demands diagnosis of many relevant characteristics, abilities and features that are thought to be predominant in the analysis of this kind of sport. Knowing all relevant anthropologic karate dimensions it is possible to select necessary instruments for measuring and to test those dimensions that karate results depend on. Considering all scientific knowledge and achievements in this field the fallowing tests are suggested: Morphologic measures: body height, arm span, arm length, pelvis width, hand ankle diameter, knees diameter, elbow diameter, body weight, parameters of one's chest, stomach, the upper and lower part of one's arm and legs, then to examine the skin fold of any sportsman's arms, back, stomach and legs. Functional diagnosis: measuring of the maximum amount of oxygen breathed in. Mobility tests: the speed of simple movements, the speed of karate technique, deep bow on the bench, shoulders capability of moving, the static strength of hands, legs, shoulders and middle part of a body, jump height, an average jump, and the percentage of maximum achievement in jumping.